Iridium–SYNPHOS-Catalyzed Hydrogenation through Dynamic Kinetic Resolution of α-Amino β-Keto Ester Hydrochlorides - Echeverria, Pierre-Georges; Férard, Charlène; Cornil, Johan; Guérinot, Amandine; Cossy, Janine; Phansavath, Phannarath; Ratovelomanana-Vidal, Virginie (Synlett, 2014)
The stereoselective synthesis of anti β-hydroxy α-amino esters by iridium–SYNPHOS-catalyzed asymmetric hydrogenation of α-amino β-keto ester hydrochlorides is reported. The reaction proceeded through dynamic kinetic resolution to afford a variety of β-hydroxy α-amino ester derivatives with good yields and high level of diastereo- and enantioselectivities (de up to 99%, ee up to 92%).
Keywords: iridium; hydrogenation; asymmetric catalysis; enantioselectivity; amino alcohols